2002
DOI: 10.1891/1058-1243.11.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Expectant Couples for New-Parent Experiences: A Comparison of Two Models of Antenatal Education

Abstract: This paper describes a pilot antenatal education program intended to better prepare couples for the early weeks of lifestyle changes and parenting. Eight weeks after birth, data were collected by questionnaire from 19 couples who participated in a pilot program and from 14 couples who were enrolled in a routine hospital program. Women in the pilot program were significantly more satisfied with their experience of parenthood. Facilitated gender-specific discussion groups formed a key strategy in the pilot progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…However, over the intervening 55 years, a shift has occurred to broaden the content of these classes to include topics such as preparation for lifestyle and relationship changes (e.g., see Fletcher, Silberberg, & Galloway, 2004;Schmied, Myors, Wills, & Cooke, 2002) and parenting education. In concert with a broadening of the curriculum, there has been a gradual inclusion of expectant fathers in these classes and, more recently, the development of gender-specific groups within antenatal programs.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, over the intervening 55 years, a shift has occurred to broaden the content of these classes to include topics such as preparation for lifestyle and relationship changes (e.g., see Fletcher, Silberberg, & Galloway, 2004;Schmied, Myors, Wills, & Cooke, 2002) and parenting education. In concert with a broadening of the curriculum, there has been a gradual inclusion of expectant fathers in these classes and, more recently, the development of gender-specific groups within antenatal programs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, the main focus has been to evaluate the effect of attendance at the classes on birth outcomes (see a review of this literature in Schmied et al, 2002). Those researchers who have investigated the role of fathers in these programs have largely found the classes wanting.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Such education has traditionally used didactic presentations to deliver information deemed important by health professionals (Myors and Mabbutt, 1997).Whilst the majority of mothers are provided with some form of breastfeeding information in Australian hospitals, in antenatal classes and breastfeeding clinics, the content and delivery is not uniform (Zareai et al, 2007). More recently, antenatal education focus has changed from women only, to include partners and family members (Schmied et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, others found that antenatal classes did not meet the needs of the male partner in relation to the emotional and psychological aspects of parenthood (Donovan, 1995). Australian researchers reported that participants in a men's only discussion group felt more comfortable making contact with other fathers than in a mixed gender group (Schmied et al, 2002). Mc Elligott's (McElligott, 2001) Scottish study (n ¼ 54) found fathers wanted information about their role and the care of their baby following delivery whilst Fletcher et al (Fletcher et al, 2004) in an Australian study of 212 fathers, suggested that fathers were prepared for childbirth, but not for lifestyle and relationship changes (Fletcher et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the models have had, as their basis, group-directed discussions (Lee & Schmied, 2001;Myors & Mabbutt, 1997;Schmied, Myors, Wills, & Cooke, 2002;Symon & Lee, 2003), slight variances have been incorporated in others. For example, Friedewald, Fletcher, and Fairbairn (2005) reported on a semistructured discussion forum that explores a range of designated topics specific to men as fathers.…”
Section: Male-specific Discussion Groupsmentioning
confidence: 99%